Metabolic Engineering of Fusarium oxysporum to Improve Its Ethanol-Producing Capability - Anasontzis, George E.; Kourtoglou, Elisavet; Villas-Boâs, Silas G.; Hatzinikolaou, Dimitris G.; Christakopoulos, Paul (Frontiers in Microbiology, 2016)
Fusarium oxysporum is one of the few filamentous fungi capable of fermenting ethanol directly from plant cell wall biomass. It has the enzymatic toolbox necessary to break down biomass to its monosaccharides and, under anaerobic and microaerobic conditions, ferments them to ethanol. Although these traits could enable its use in consolidated processes and thus bypass some of the bottlenecks encountered in ethanol production from lignocellulosic material when Saccharomyces cerevisiae is used—namely its inability to degrade lignocellulose and to consume pentoses—two major disadvantages of F. oxysporum compared to the yeast—its low growth rate and low ethanol productivity—hinder the further development of this process. We had previously identified phosphoglucomutase and transaldolase, two major enzymes of glucose catabolism and the pentose phosphate pathway, as possible bottlenecks in the metabolism of the fungus and we had reported the effect of their constitutive production on the growth characteristics of the fungus. In this study, we investigated the effect of their constitutive production on ethanol productivity under anaerobic conditions. We report an increase in ethanol yield and a concomitant decrease in acetic acid production. Metabolomics analysis revealed that the genetic modifications applied did not simply accelerate the metabolic rate of the microorganism; they also affected the relative concentrations of the various metabolites suggesting an increased channeling towards the chorismate pathway, an activation of the γ-aminobutyric acid shunt, and an excess in NADPH regeneration.